2021
DOI: 10.1186/s12943-021-01335-5
|View full text |Cite
|
Sign up to set email alerts
|

mRNA vaccine for cancer immunotherapy

Abstract: AbstractmRNA vaccines have become a promising platform for cancer immunotherapy. During vaccination, naked or vehicle loaded mRNA vaccines efficiently express tumor antigens in antigen-presenting cells (APCs), facilitate APC activation and innate/adaptive immune stimulation. mRNA cancer vaccine precedes other conventional vaccine platforms due to high potency, safe administration, rapid development potentials, and cost-effective manufacturing. However, mRNA vaccine applications have been limited by instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
529
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 594 publications
(530 citation statements)
references
References 149 publications
0
529
0
1
Order By: Relevance
“…The rationale for developing mRNA-based vaccines for cancer immunotherapy is not to prevent cancer but to destroy tumor cells in the patient [ 1 , 2 ]. Initial preclinical studies on mRNA vaccines were conducted in animal models and showed efficacy that was not supported in clinical studies [ 2 , 3 ]. In the past decade, there have been rapid developments in checkpoint inhibitors, vaccine adjuvants, vaccine delivery systems, and increased understanding of the tumor microenvironment, including the roles of antigen-presenting cells (APCs) [ 4 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale for developing mRNA-based vaccines for cancer immunotherapy is not to prevent cancer but to destroy tumor cells in the patient [ 1 , 2 ]. Initial preclinical studies on mRNA vaccines were conducted in animal models and showed efficacy that was not supported in clinical studies [ 2 , 3 ]. In the past decade, there have been rapid developments in checkpoint inhibitors, vaccine adjuvants, vaccine delivery systems, and increased understanding of the tumor microenvironment, including the roles of antigen-presenting cells (APCs) [ 4 ].…”
mentioning
confidence: 99%
“…Other challenges to mRNA vaccine development included the instability of mRNA and its low immunogenicity, which initially resulted in poor immune responses [ 4 ]. These initial challenges were overcome by mRNA sequence optimization, and current advantages of mRNA vaccines include their safety and efficacy and the ability for manufacturing on a mass scale [ 3 , 4 ],…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All four use coding sequences for the spike protein. The latest developments will certainly also contribute to our fight, not only against other types of viral infections, but also against cancer ( Pardi et al, 2018 ; Zhang et al, 2019 ; Xu et al, 2020b ; Miao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The technology of mRNA vaccination offers promising prophylactic and therapeutic potentials in several medical fields including immuno-oncology [4]. Therefore, current oncological clinical trials should consider the potential theranostic value of [18F]-FDG PET and correlate temporal changes in glucose metabolism of lymphoid tissues with treatment outcome.…”
mentioning
confidence: 99%